RANCANG BANGUN MESIN PEMOTONG PIPA DENGAN LAS OXY ACETYLENE - Ariksa, Jeri; Setiawan, Yudi; Kadriadi, Kadriadi; Amiruddin, Amiruddin; Pratama, Angga Bahri (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2023)
Metal cutting is the stage of processing profile raw materials and steel plates according to the cut marks that have been set in the marking process. One of the metal cutting techniques is to use oxy acetylene welding where the cutting occurs due to the reaction of oxygen and steel. Oxy acetylene welding is a manual cutting and welding process, in which the surfaces to be joined are heated until melted by the flame of acetylene gas, namely burning C₂H₂ with O₂ with filler metal or without filler metal where the joining process is without pressure. Besides for welding purposes (connection), oxy acetylene welding can also be used as preheating, brazing, cutting and hard facing. In the process of cutting iron pipes using oxy acetylene welding manually, the problem that is often found is the results of uneven and not straight cuts. This causes a leveling process to be needed on the edges that are cut so that they are flat and straight. In this research, a pipe cutting machine with oxy acetylene welding has been made which aims to produce straight, smooth, and even pipe cutting. The pipe cutting machine that has been made can produce flat, smooth, and straight iron pipe cuts on iron pipes with a diameter of 4.5 inches, 3.5 inches and 3 inches with a cutting time of 32 seconds, a motor wave rotation speed of 5.8 Hz, and a cut tolerance of ± 3 mm.